Controls on Open‐Ocean North Atlantic ΔpCO2 at Seasonal and Interannual Time Scales Are Different. Issue 17 (6th September 2018) - Henson, Stephanie A.; Humphreys, Matthew P.; Land, Peter E.; Shutler, Jamie D.; Goddijn‐Murphy, Lonneke; Warren, Mark
Abstract: The North Atlantic is a substantial sink for anthropogenic CO2 . Understanding the mechanisms driving the sink's variability is key to assessing its current state and predicting its potential response to global climate change. Here we apply a time series decomposition technique to satellite and in situ data to examine separately the factors (both biological and nonbiological) that affect the sea‐air CO2 difference (Δ p CO2 ) on seasonal and interannual time scales. We demonstrate that on seasonal time scales, the subpolar North Atlantic Δ p CO2 signal is predominantly correlated with biological processes, whereas seawater temperature dominates in the subtropics. However, the same factors do not necessarily control Δ p CO2 on interannual time scales. Our results imply that the mechanisms driving seasonal variability in Δ p CO2 cannot necessarily be extrapolated to predict how Δ p CO2, and thus the North Atlantic CO2 sink, may respond to increases in anthropogenic CO2 over longer time scales. Plain Language Summary: As atmospheric carbon dioxide (CO2 ) concentrations rise due to anthropogenic emissions, the ocean is taking up more CO2, a process known as the oceanic CO2 sink. The North Atlantic is a major anthropogenic CO2 sink; however, factors that drive variability in the sink are still under investigation. In order to assess the sink's current state and future with continued climate change, we need to understand what affects the North Atlantic CO2 sink. Often, the factors that affect oceanic uptake of CO2 are explored on a seasonal time scale. Here we take a longer view, examining the factors that may affect ocean uptake on interannual time scales. We find that the factors are different, depending on whether we assess the short or long term. In building models of ocean response to future climate change, we cannot extrapolate the response of ocean CO2 uptake to seasonal variability out to longer time scales. Key Points: Observational evidence shows that the mechanisms underlying seasonal variability in Δ p CO2 are not the same as those underlying interannual variability The presence of a vigorous spring bloom and the resultant phytoplankton succession dominate seasonal Δ p CO2 in subpolar waters Long‐term observations of ocean CO2 are required to distinguish seasonal and interannual controls on Δ p CO2